CATUR PIWULANG: THE CONCEPT OF GREAT LEADERS IN JAVANESE PARADIGM - Hastuti, Nuri Puji (UI Scholars Hub, 2026)
Leaders can be a key factor in determining whether a nation experiences a flourishing or declining period. However, numerous phenomena indicate that Indonesia is losing its great leaders. Based on this problem, this research aims to explain and describe the forms, meanings, and functions of catur piwulang as the concept of great leaders in the Javanese paradigm. A descriptive qualitative method has been used. The syntax consists of data collection, reduction, display data, and conclusion. Data validity was checked through the triangulation of theories, resources, and techniques. The forms of catur piwulang are 1) wewehono teken, teken wong kalunyon, 2) wewehono pangan, pangan wong kaluwen, 3) wewehono sandang, sandang wong kawudan, 4) weweh payung wong kudanan. The meaning of those forms are 1) leaders need to establish regulations or laws that reflect the truth principle, such as the Quran, hadith, and the truth value of their citizens, so that both governments and citizens can use it as an ethical principle to guide their thoughts, actions, and behavior, 2) leaders need to establish regulations to help their citizens fulfill basic needs, such as access to quality food, education, infrastructure, and a stable economic environment, 3) leaders need to enact laws to protect their citizens from various crimes and ensure that their citizens can practice their religions freely, 4) leaders must ensure that the laws or regulations are adequately enforced and correctly. The functions of catur piwulang are 1) the concept of teken, which refers to the truth principle, such as Al-Quran and hadith, and the truth value for wong kang kalunyon, can function as an ethical principle for governments and citizens to guide their thoughts, actions, and behavior, 2) the concept of pangan and wong kang kaluwen can function as advice for leaders to create regulations that fulfill the basic needs of their citizens, such as good quality food, education, infrastructure, and a stable economic environment, 3) sandang for wong kang kawudan, as one of the concepts in catur piwulang, can function as advice for leaders to make laws that protect their citizens from various crimes and ensure that their citizens can practice their religions freely, 4) payung for wong kang kudanan can function as advice for leaders to ensure that laws or regulations are adequately enforced and correctly.